Dynamic electrocatalyst with current-driven oxyhydroxide shell for rechargeable zinc-air battery - Deng, Ya-Ping; Jiang, Yi; Liang, Ruilin; Zhang, Shao-Jian; Luo, Dan; Hu, Yongfeng; Wang, Xin; Li, Jun-Tao; Yu, Aiping; Chen, Zhongwei (Nature communications, 2020)
Recent fruitful studies on rechargeable zinc-air battery have led to emergence of various bifunctional oxygen electrocatalysts, especially metal-based materials. However, their electrocatalytic configuration and evolution pathway during battery operation are rarely spotlighted. Herein, to depict the underlying behaviors, a concept named dynamic electrocatalyst is proposed. By selecting a bimetal nitride as representation, a current-driven “shell-bulk” configuration is visualized via time-resolved X-ray and electron spectroscopy analyses. A dynamic picture sketching the generation and maturation of nanoscale oxyhydroxide shell is presented, and periodic valence swings of performance-dominant element are observed. Upon maturation, zinc-air battery experiences a near two-fold enlargement in power density to 234 mW cm −2 , a gradual narrowing of voltage gap to 0.85 V at 30 mA cm −2 , followed by stable cycling for hundreds of hours. The revealed configuration can serve as the basis to construct future blueprints for metal-based electrocatalysts, and push zinc-air battery toward practical application. Interest in rechargeable Zn-air batteries has been renewed in recent years, however, their oxygen electrocatalysts remain not fully understood. Here the authors reveal the presence of a current-driven oxyhydroxide shell in a so-called dynamic eletrocatalyst that enables optimized battery performance.